2019
DOI: 10.21037/jgo.2019.01.26
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy in oesophageal cancer with positive circumferential resection margins—recurrence and survival outcomes

Abstract: Background: The role of adjuvant radiotherapy in patients with microscopically positive circumferential resection margins (CRM), R1 specimen, in oesophageal resections for cancer with curative intent remains unclear. However, R1 specimens are associated with poorer survival outcomes. The aim was to assess the benefit of adjuvant radiotherapy on recurrence and survival in these patients. Methods: Patients were identified in a single centre between July 2000 and December 2016. Patient demographics, tumour charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Conversely, others have suggested that there is no role for adjuvant radiation. In a cohort of 68 esophageal R1 patients, Vadhwana et al did not find any RFS or OS benefit Patient clinical status 7 [21] Postoperative complications prohibiting treatment 5 [15] Deemed not indicated by oncologist 8 [24] Patient preference 4 [12] Metastatic disease on postoperative imaging 3 [9] Other in patients who received postoperative radiation compared to those who did not (21).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, others have suggested that there is no role for adjuvant radiation. In a cohort of 68 esophageal R1 patients, Vadhwana et al did not find any RFS or OS benefit Patient clinical status 7 [21] Postoperative complications prohibiting treatment 5 [15] Deemed not indicated by oncologist 8 [24] Patient preference 4 [12] Metastatic disease on postoperative imaging 3 [9] Other in patients who received postoperative radiation compared to those who did not (21).…”
Section: Discussionmentioning
confidence: 99%